1987
DOI: 10.1007/bf01026203
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the purified multifunctional cellulase component of Penicillium funiculosum

Abstract: The endoglucanase component (CMCase I) ofPenicillium funiculosum cellulase was purified to apparent homogeneity by ultrafiltration and gel chromatography. It consists of a single polypeptide chain with a molecular weight of 56000 and is a glycoprotein. Viscometric and end-product analysis revealed the randomness of enzyme action. Multifunctional characteristic of CMCase I was studied with various carbohydrate substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…In addition to the complexity of the multi-enzymatic system, the variability of the enzymatic assays reported in literature made it difficult to compare the K mapp values of cellulases from different sources. Nevertheless, the K mapp (Table 1) of the endo-1,4-β-D-glucanase (3.55 mg mL -1 ) was lower than that reported (33) for the same enzyme from another P. funiculosum strain (20 mg mL -1 ); however, close K mapp values (2.0-4.8 mg mL -1 ) have been reported (27) for two isoenzymes of endo-1,4-β-Dglucanase from P. pinophilum. On the other hand, the K mapp of cellobiohydrolase (2.59 mM) was higher than that reported for the same enzyme from another P. funiculosum strain (0.85 mM), using cello-oligosaccharide as substrate (6).…”
Section: Resultscontrasting
confidence: 66%
“…In addition to the complexity of the multi-enzymatic system, the variability of the enzymatic assays reported in literature made it difficult to compare the K mapp values of cellulases from different sources. Nevertheless, the K mapp (Table 1) of the endo-1,4-β-D-glucanase (3.55 mg mL -1 ) was lower than that reported (33) for the same enzyme from another P. funiculosum strain (20 mg mL -1 ); however, close K mapp values (2.0-4.8 mg mL -1 ) have been reported (27) for two isoenzymes of endo-1,4-β-Dglucanase from P. pinophilum. On the other hand, the K mapp of cellobiohydrolase (2.59 mM) was higher than that reported for the same enzyme from another P. funiculosum strain (0.85 mM), using cello-oligosaccharide as substrate (6).…”
Section: Resultscontrasting
confidence: 66%
“…The overall results indicate that the endo-1,3-1,4--D-glucanase specific activity exhibited higher thermal stability than that of endo-1,4--D-xylanase. Similarly, Sahasrabudhe et al 35) have reported that the thermal stability of endoglucanase from P. funiculosum was greater than that of the endo-1,4--D-xylanase. The experimental findings (Fig.…”
Section: )mentioning
confidence: 99%
“…The CBH belongs to three different glycoside hydrolase families namely GH6, GH7 and GH48. The importance of two cellobiohydrolases, CBH1 and CBHII has been realized for their preferences to act on the reducing and nonreducing ends of cellulose chains of microcrystalline cellulose [14,29,32] In fungi, the presence of CBH1 is needed for ordered degradation of cellulose, which requires all three structural modules of the cellulase i.e., the CD, C-terminal CBD, and linker region [33]. The fungus Penicillium funiculosum is a filamentous fungus an efficient producer of cellulase [34] [27].…”
Section: Introductionmentioning
confidence: 99%